Ground Response Analysis for Two Selected Sites in Al-Hilla City in the Middle of Iraq (Journal of University of Babylon for Engineering Sciences, 2018)
Ground response analysis also termed as soil amplification study comprises the calculation of site natural periods, ground motion amplification, evaluation of liquefaction potential, and stability analysis. The important features that are considered for analysis are characteristics of soil overlying bedrock, bedrock location and inclination, topography of bedrock and soil deposits, faults in the soil deposits.In this paper, two sites within Al-Hilla city were selected to investigate the ground response analysis. Laboratory tests  included moisture content, Aterbberg limits , and  the  grain size distribution curves have been developed to understand the particle size distribution of the alluvium present, while field work included: shear wave velocity measurements and N-value calculation.From geotechnical characterization, it has been observed that the soil profile in the two sites is dominated by silty sand and silty clay. The site response analysis of ground motion was carried out using Proshake software. The results of the equivalent linear analysis show that the peak surface ground acceleration ranges between 0.0523g to 0.0639g. The amplification factor for acceleration is in the range between 1.048 to 1.27.